Relationships Between Jianghuai Meiyu Anomaly and the Collaborative Evolution of Wave Trains in the Upper and Lower Troposphere in Mid-July of 2020 - Wang, Junyu (Frontiers in Earth Science, 2020)
Based on the ECMWF reanalysis dataset (ERA5), SST , OLR and the daily precipitation data, the relationship between the Meiyu anomaly in the Yangtze-Huaihe river basin (YHB) and the collaborative evolution of wave trains in the upper and lower troposphere in the mid-July of 2020 is analyzed. The results show that the key circulation background for the long-lasting Meiyu season in the summer of 2020 is the coexistence and collaborative evolution of the "– + –" Silk-Road (SR) wave train in the upper troposphere and the "+ – +" Pacific-Japan (PJ) wave train in the middle-lower troposphere, which is in favor of the movement towards each other of the South Asia high (SAH) and the western Pacific subtropical high (WPSH), resulting in the upper-level divergence over the YHB where is the right side of the jet entrance area. The WPSH strengthens and extends westward, transporting abundant water vapor to the YHB from the Western Pacific and South China Sea. Meanwhile, the meridional circulation develops at the middle and high latitudes, which is in favor of cold-dry air and warm-moist air strongly interact over the YHB, leading to the long-lasting Meiyu season. The coordinative evolution of the SR and PJ wave trains not only affects the persistence and intensity of precipitation in the YHB, but also can be regarded as a precursor signal for the occurrence of persistent heavy rainfall to some extent. The wave-activity flux dispersing eastward along the upper-level jet is beneficial to the development and maintenance of the SR wave train, and the poleward dispersing wave-activity flux is related to the development and maintenance of the PJ wave train. Additionally, along with the weakening El Nino in 2019, the anomalous convection caused by the warm SST in the Western Pacific warm pool is conducive to the formation and maintenance of the PJ wave train. The abnormal convection caused by the warm SST in the Indian Ocean and the east coast of the tropical Atlantic may affect the SR wave train. These are also one of the reasons for the long Meiyu season in 2020.